Social inclusion in the neighbourhood and the professional role identity of group home staff members: views and experiences of staff regarding neighbourhood social inclusion of people with intellectual disabilities. Issue 1 (1st January 2017) - Overmars-Marx, Tessa; Thomése, Fleur; Meininger, Herman
ABSTRACT: During the last decades, people with intellectual disabilities have moved to regular neighbourhoods and policies have incorporated goals related to social inclusion. However, people with intellectual disabilities are still experiencing social isolation. We investigated the role of group home staff members, on the assumption that neighbourhood social inclusion cannot be considered a standard element of their professional role identity. The aim of our study was to gain insight into the individual perceptions of staff and the institutional environment in relation to staff's professional role identity in dealing with neighbourhood social inclusion. We conducted semi-structured group interviews with staff from nine group homes in three neighbourhoods in the Netherlands. Our analysis yielded five themes: 1) staff perceptions of residents' neighbourhood contacts: positive and negative experiences; 2) staff perceptions of residents' needs and capabilities; 3) staff perceptions of neighbours and neighbourhood; 4) staff perceived role in social inclusion in the neighbourhood; and 5) staff perceived role of service provider. Our study showed that individual perceptions of a professional role identity primarily focused on care tasks, and the (lack of) experienced support from service providers hinders staff in creating opportunities for social inclusion in the neighbourhood. To enhance social inclusion in the neighbourhood we recommend service providers invest in supporting staff in acquiring the necessary skills.